Maternal Xp22.31 copy-number variations detected in non-invasive prenatal screening effectively guide the prenatal diagnosis of X-linked ichthyosis - Tang, Xinxin; Wang, Zhiwei; Yang, Shuting; Chen, Min; Zhang, Yue; Zhang, Fang; Tan, Juan; Yin, Ting; Wang, Leilei (Frontiers in Genetics, 2022)
Background and aims: X-linked ichthyosis (XLI) is a common recessive genetic disease caused by the deletion of steroid sulfatase (STS) in Xp22.31. Maternal copy-number deletions in Xp22.31 (covering STS) can be considered an incidental benefit of genome-wide cell-free DNA profiling. Here we explored the accuracy and clinical value of maternal deletions in Xp22.31 during non-invasive prenatal screening (NIPS). Materials and methods: We evaluated 13,156 pregnant women who completed NIPS. The Maternal deletions in Xp22.31 revealed by NIPS were confirmed with maternal white blood cells by chromosome microarray analysis (CMA) or copy-number variation sequencing (CNV-seq). Suspected positive women pregnant with males were informed and provided with prenatal genetic counseling. Results: Nineteen maternal deletions in Xp22.31 covering STS were detected by NIPS, which were all confirmed, ranging in size from 0.6–1.76 Mb. Among them, eleven women with deletions in male fetuses accepted prenatal diagnoses and finally nine cases of XLI were diagnosed. The nine XLI males had differing degrees of skin abnormalities, and of them, some male members of six families had symptoms associated with XLI. Conclusion: NIPS has the potential to detect clinically significant maternal X chromosomal CNVs causing XLI, which can guide the prenatal diagnosis of X-linked ichthyosis and reflect the family history, so as to enhance pregnancy management as well as children and family members’ health management.